Selenium’s Significance for Human Health and Its Potential Anti-Oncogenic Properties: A Literature Review - Fabijański, Artur; Konarska, Anna; Machowiak, Anna; Ufnalska, Barbara; Lisiecka, Justyna; Janik, Mateusz; Nowak, Michał; Rychlewska-Duda, Joanna; Firlej, Wojciech; Dukacz, Adriana (Journal of Education, Health and Sport, 2025)
Introduction Selenium (Se), an essential trace element, has attracted considerable attention due to its multifaceted roles in human health, particularly its potential anti-oncogenic properties. This literature review aims to synthesise current knowledge regarding the biological functions of Se, its association with cancer risk, and the efficacy of Se supplementation in the prevention and treatment of cancer. The review provides a critical evaluation of the evidence derived from epidemiological studies, randomised controlled trials (RCTs), and mechanistic investigations, elucidating areas of consensus and divergence within the existing literature. Furthermore, it underscores the roles of Se in additional domains of human health, including cardiology, neurology, and endocrinology.